Fertilizer Effects on Some Properties of Two Major Soil Series of Sudan - Elamin, A E; Elagih, M A (Annals of Arid Zone, 2016)
Residual effects of organic and inorganic fertilizers on some physical and chemical properties of Vertisols and Aridisols of Sudan were studied during 1995-96 and 1996-97 seasons in a completely randomized design. Fertilizers significantly improved the saturated hydraulic conductivity of the two soils. The organic fertilizers were more effective than inorganic fertilizers. and the effects were more pronounced for Vertisols compared to Aridisols. The organic fertilizers significantly decreased the soil pH. Green and poultry manures significantly reduced the electrical conductivity of the saturation extract (ECe). The applied green manure. poultry manure and urea significantly increased Ca and Mg contents. whereas. the other treatments significantly reduced them. The organic manures used may be considered comparable in increasing Ca and Mg contents. Poultry manure significantly increased the Na content. and in Vertisols Na content exceeded that in Aridisols. The K content was not significantly affected by the treatments and it was less in Vertisols compared to Aridisols. The sodium adsorption ratio was significantly reduced by the treatment, whereas the Ca:Mg ratio was significantly improved by poultry manure, urea and superphosphate treatments. There was a significant correlation between Ca:Mg and ECe (r = + 0.60) and P was negatively correlated with soil pH (r= -0.11). There was no significant difference in N contents of the two soils. The data also revealed that poultry manure, superphosphate and NPK significantly increased the P content. The amount of P in Aridi,ols exceeded that of Vertisols.